COMPARATIVE ANALYSIS OF CRITICAL THINKING USINFG PROBLEM-BASED LEARNING (PBL) AND PREDICT OBSERVE EXPLAIN (POE) MODELS IN CELL MATERIAL - Pranoto, Hendro (Universitas Negeri Medan, 2024)
This study aims to examine the difference in critical thinking abilities using the Problem-Based Learning (PBL) and Predict-Observe-Explain (POE) models in the topic of cells. The research design employed in this study is quasi-experimental with a Nonequivalent Control Group design. The population in this research consists of two classes of XI IPA, totaling 60 students. Sampling was conducted using the Saturation sampling technique. The instrument used to measure critical thinking abilities was a set of ten essay-type questions. The average scores of pretest and posttest critical thinking abilities of students using the POE and PBL models were as follows, respectively: 54.83; 72.75 and 52.67; 78.83. The data results for critical thinking abilities across 5 indicators using the PBL and POE models were 79.90 and 71.50, respectively, categorized as high. The t-test results indicate that critical thinking abilities using the PBL model are superior to those using the POE model. The N-gain test results reveal that both models are equally effective in enhancing students' critical thinking abilities.